2007
DOI: 10.1523/jneurosci.4128-06.2007
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiological Mechanisms Involved in Transfer of Procedural Knowledge

Abstract: Learning to perform a motor task with one hand results in performance improvements in the other hand, a process called intermanual transfer. To gain information on its neural mechanisms, we studied this phenomenon using the serial reaction-time task (SRTT). Sixteen, right-handed volunteers trained a 12-item sequence of key presses repeated without the subjects' knowledge. Blocks with no repeating sequence, called random blocks, were interspersed with sequence-training blocks. Response times improved in random … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
148
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(173 citation statements)
references
References 70 publications
25
148
0
Order By: Relevance
“…This is consistent with findings showing that during a strong unimanual contraction it is more likely to have the presence of mirror EMG activity than during small efforts (Zijdewind et al, 2006). In other unimanual tasks, the existence of disinhibition in the M1 ipsilateral may vary depending on the behavioral context: distal versus proximal muscles involved (Harris-Love et al, 2007), level of complexity of the movement (Avanzino et al, 2008) and learning related improvements (Chen et al, 1997;Davare et al, 2007;Duque et al, 2007;Perez et al, 2007). On the other side, the activity-dependent changes in IHI-SICI identified here may provide insights to better understand unwanted mirror EMG activity in the opposite limb, which is frequently reported during unimanual movements in patients with motor disorders (Hashimoto et al, 2001;Georgiou-Karistianis et al, 2004;Cincotta and Ziemann, 2008).…”
Section: Ihi From M1 Contralateral To M1 Ipsilateralsupporting
confidence: 87%
See 1 more Smart Citation
“…This is consistent with findings showing that during a strong unimanual contraction it is more likely to have the presence of mirror EMG activity than during small efforts (Zijdewind et al, 2006). In other unimanual tasks, the existence of disinhibition in the M1 ipsilateral may vary depending on the behavioral context: distal versus proximal muscles involved (Harris-Love et al, 2007), level of complexity of the movement (Avanzino et al, 2008) and learning related improvements (Chen et al, 1997;Davare et al, 2007;Duque et al, 2007;Perez et al, 2007). On the other side, the activity-dependent changes in IHI-SICI identified here may provide insights to better understand unwanted mirror EMG activity in the opposite limb, which is frequently reported during unimanual movements in patients with motor disorders (Hashimoto et al, 2001;Georgiou-Karistianis et al, 2004;Cincotta and Ziemann, 2008).…”
Section: Ihi From M1 Contralateral To M1 Ipsilateralsupporting
confidence: 87%
“…fMRI (Dettmers et al, 1995;Thickbroom et al, 1998;Dai et al, 2001;van Duinen et al, 2008) and TMS (Hess et al, 1986;Stedman et al, 1998;Tinazzi and Zanette, 1998;Muellbacher et al, 2000;Hortobagyi et al, 2003) studies in humans revealed functional changes in M1 ipsilateral during parametric increases in unimanual force. Additionally, motor learning studies have demonstrated the involvement of M1 ipsilateral during acquisition of unimanual motor skills (Chen et al, 1997;Davare et al, 2007;Duque et al, 2007;Perez et al, 2007). Although increasing evidence points to the involvement of M1 ipsilateral during performance of a unimanual motor task, the neuronal mechanisms controlling the corticospinal output originated in the M1 ipsilateral and the resting hand remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that increased MEP amplitude in the trained hand probably reflects alterations in the properties of circuitry in M1, and/or changes in the effectiveness of inputs to M1 from distant cortical areas. For example, Perez et al (32) recently showed that the supplementary motor area is crucially important in the expression of cross-limb transfer of sequence learning performance. In contrast, there is no direct evidence to indicate the site of neural adaptation underlying the increase in corticospinal excitability for the untrained hand.…”
Section: Discussionmentioning
confidence: 99%
“…This effect has been variously termed "cross-transfer," "cross-education," and "interlimb transfer," and it has been demonstrated for a wide range of motor tasks including mirror tracing, movement tasks under visuomotor rotations and novel force field conditions, execution of multifinger tapping sequences, exertion of maximal force, and tasks requiring fine control of movement timing and force (e.g., Refs. 3,11,32,33,41,43,44). Most theoretical attempts to account for cross-transfer are based on the idea that the neural adaptations underlying improved performance with the trained limb must reside at a central nervous system (CNS) site that is also accessible for the control of the contralateral limb (e.g., Refs.…”
mentioning
confidence: 99%
“…This effect is further enhanced when movement observation is combined with physical practice (Celnik et al, 2006Stefan et al, 2008). Neural changes due to use-dependent plasticity involve the primary motor cortex (M1) and can be quantified by transcranial magnetic stimulation (TMS) (Classen et al, 1998;Perez et al, 2007;Rosenkranz et al, 2007a,b). Physical motor training leads to larger motor-evoked potentials (MEPs) for a given stimulation intensity, indicating an increase in corticomotor excitability.…”
Section: Introductionmentioning
confidence: 99%